FORMULATION AND DEVELOPMENT OF DELAYED RELEASE TABLETS OF BETULINIC ACID - P.MURALI KISHAN, (International Journal of Pharma and Bio Sciences, 2014)
Purpose: Colonic drug delivery has gained increased importance for the delivery of drugs, proteins and therapeutic peptides. Drugs to reach the colonic region unchanged they must be protected in upper GIT (stomach & intestinal regions.. The present study is for development of colon targeting Betulinic acid tablets using compression coating method using different combinations of Gums, organic and inorganic solvents. Preformulation, weight variation, content uniformity and invitro dissolution studies were performed using USP apparatus II. Mediums of different pH and microflora medium were used. Results: Hardness 4kg/cm2 (core) & 5kg/cm2 (coated), gums in combination showed better results than when used alone. F1, F2, F3 failed in early stages of evaluation tests. Release rates end of 5 hours (F4=3.17%, F5=2.69%, F6=4.04%, F7=1.92%) & at end of 17 hours (F4=82.54%, F5=98.06%, F6=88.16%, F7=99.7%). Conclusion: colon delivery can be achieved using combination of guar gum & xanthan gum combinations or combination of 3 gums including tamarind gum.